Condom migration after introduction of pre-exposure prophylaxis among HIV-uninfected adolescents in South Africa: A cohort analysis - Lennart P. Maljaars; Katherine Gill; Philip J. Smith; Glenda E. Gray; Janan J. Dietrich; Gabriela B. Gomez; Linda-Gail Bekker (AOSIS, 2017)
Background: Approximately 3 million adolescents and young adults (AYA), between the ages of 15 years and 24 years, are living with HIV in sub-Saharan Africa. The use of pre-exposure prophylaxis (PrEP) may be a promising HIV prevention tool to bridge the high-risk years of AYA between sexual debut and adulthood. Objectives: Concerns have been raised that the use of PrEP could lead to an increase in sexual risk behaviour and sexually transmitted infections in general and less condom use in particular among adolescents. Methods: This study assesses condom use among South African adolescents enrolled on a demonstration PrEP study, called Pluspills, being conducted in Cape Town and Soweto. A questionnaire on sexual risk behaviour was administered at baseline and after 4, 8 and 12 weeks. Three different questions on condom use were asked at each visit. Unless all answers indicated condom use at all times, a participant was scored 'at risk'. McNemar's tests and a Cochran's Q test were used to investigate changes in condom use over time. Results: We interviewed 148 adolescents (66% female) at baseline. Eighty-nine participants completed all visits. In this group, an increase in condom use was observed over the period of 12 weeks. Most participants who reported behavioural changes mentioned an increase in condom use. Conclusion: There was no sign of sexual risk compensation in the 12 weeks of the study. Observed increase in condom use can be explained by an increased awareness of personal HIV risk or by social desirability or recall biases. In future research, additional data including other biomarkers of unprotected sex and longer follow-up time would be useful to help understand the relationship between PrEP use, sexual risk perception and consequent behaviours, especially in adolescents.